DESCRIPTION OF PARTIALLY EDENTULOUS PATTERN AMONG PATIENTS AT RSGMP GUSTI HASAN AMAN IN BANJARMASIN - Huda Ainani; Rahmad Arifin; Ika Kusuma Wardani (FKG Unlam, 2021)
ABSTRACTBackground: Partial edentulism is the process when single or multiple teeth is missing from the alveolar socket and it may become an indicator for oral health. Partial edentulism can occur since the age of six and the aging factor increases the risk. Partial edentulism can be caused by some factors including: ages, gender, economic level, education level, knowledge level, and the etiology of the tooth loss. Purpose: To describe the distribution of partially edentulous pattern from RSGMP Gusti Hasan Aman’s patients in Banjarmasin. Method: This study was including patients from RSGMP Gusti Hasan Aman between the age of 17-45 years old in Banjarmasin using purposive sampling. Questionnaires were distributed to determined patient knowledge on oral health with Kennedy classification for the partially edentulous pattern. Result: Kennedy Class II was the most frequent edentulous pattern observed on the upper (37%) and the lower jaw (39%). In particular, the adolescent group had the highest percentage (43%) of partial edentulism based on age. Women had the highest percentage (57%) of partial eduntulism based on gender. Respondents with moderate economic status had the highest percentage (35%) of partial edentulism. Respondents that have high school or above education level were the highest percentage (87%) identified with partial edentulous. The most common etiology that identified with partial edentulous was the caries (52%). Conclusion: It can be concluded that Kennedy class III is the most confronted partially edentulous pattern among patients at RSGMP Gusti Hasan Aman in Banjarmasin.Keywords: Partially Teeth Loss Pattern, Kennedy, RSGMP Gusti Hasan Aman